2016
DOI: 10.1002/open.201600081
|View full text |Cite
|
Sign up to set email alerts
|

Valosin‐containing Protein is a Target of 5′‐l Fuligocandin B and Enhances TRAIL Resistance in Cancer Cells

Abstract: Fuligocandin B (2) is a novel natural product that can overcome TRAIL resistance. We synthesized enatiomerically pure fuligocandin B (2) and its derivative 5′‐I fuligocandin B (4), and found that the latter had an improved biological activity against the human gastric cancer cell line, AGS. We attached a biotin linker and photoactivatable aryl diazirine group to 5′‐I fuligocandin B (4), and employed a pull‐down assay to identify valosin‐containing protein (VCP/p97), an AAA ATPase, as a 5′‐I fuligocandin B (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…These authors identified VCP/p97 as a target protein of 5′-I fuligocandin B, a natural product that overcomes TRAIL resistance. VCP/p97 knockdown in AGS cells induced TRAIL sensitivity, the overexpression of CHOP and DR5 proteins, and subsequent TRAIL-induced cell death [ 75 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These authors identified VCP/p97 as a target protein of 5′-I fuligocandin B, a natural product that overcomes TRAIL resistance. VCP/p97 knockdown in AGS cells induced TRAIL sensitivity, the overexpression of CHOP and DR5 proteins, and subsequent TRAIL-induced cell death [ 75 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…Thus, VCP/p97 represents a potential prognostic biomarker and a therapeutic target. [71] Gastric cancer greater tumor size, presence of vascular and lymphatic invasion, lymph node metastasis, and shorter overall and disease free survival [72] cell survival, degradation of cellular regulators, and gastric carcinogenesis [73,74] low levels of CHOP and DR5 [75] Esophageal cancer higher frequencies of lymph node metastasis, deeper invasion, metastasis, and shorter disease free and overall survival [76] shorter overall survival [77] Breast cancer shorter overall survival [78] poor outcomes of triple-negative patients receiving chemotherapy [79,80] Hematological cancer tumor grade, stage, histological subtype, recurrence and shorter overall and disease-free survival of patients with B-cell lymphoma [104] multiple myeloma development and progression [105] poor prednisone responders in pediatric patients with acute lymphoblastic leukemia [106] exosome generation and secretion in Jurkat tumor cells [107] Melanoma advanced radiotherapy [108] immune escape [109] Glioblastoma radiosensitivity of glioblastoma cells, and survival time of xenografted mice with radiation treatment [110,111] HDAC6 levels and temozolomide resistance therapy [112] Ovarian cancer chemotherapy response in patients receiving the platinum-taxane combination [113] Testicular cancer development of different types of human testicular tumors [114] Bladder cancer shorter survival following bladder removal by cystectomy [115] Squamous cell carcinoma development of squamous cell carcinoma [116] 3.1. VCP/p97 in Gastrointestinal Cancers 3.1.1.…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…However, Withaferin A 27-Acetate exhibited anti-proliferative effects in cancer cell lines at 10-fold lower concentration, suggesting additional modes of action. Clotrimazole [37], Oxaspirol B [38], and 5'-I-Fuligocandin B [39] exhibited p97 inhibition activity with IC 50 values of 12 μM, 31.2 ± 3.0 μM and 7.0 μM, respectively. However, their mechanisms of action are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…2). Fuligocandin B (2) has the ability to overcome TRAIL resistance in T-cell leukemia/lymphoma 7) and human gastric adenocarcinoma (AGS) cells, 8) however fuligocandin B (2) did not show the cytotoxicity against peripheral blood mononuclear cells. 7) Recently, we identified valosin-containing protein (VCP) as a target protein of 5′-I fuligocandin B (3) and elucidated the mechanism of the activity for overcoming TRAIL resistance.…”
mentioning
confidence: 99%
“…7) Recently, we identified valosin-containing protein (VCP) as a target protein of 5′-I fuligocandin B (3) and elucidated the mechanism of the activity for overcoming TRAIL resistance. 9) 5′-I fuligocandin B (3) inhibits VCP function along with inducing accumulation of ubiquitinated proteins, which causes endoplasmic reticulum (ER) stress. The expression of DR5 is increased by accumulation of CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP), a transcription factor for DR5, which is induced by ER stress.…”
mentioning
confidence: 99%